Effect of gum arabic concentrations on drying kinetics, anthocyanin degradation and product qualities of purple rice bran extract dried by foam-mat technique - L.T.K. Loan; Bùi Thế Vinh; Ngô Văn Tài (Revista Mexicana de Ingeniería Química, 2023)
Derivation and application of
Keywords: Food Quality and Safety Studies; Food composition and properties